2019
DOI: 10.18632/aging.101719
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma ceramide levels in post-menopausal women: a cross-sectional study

Abstract: Circulating ceramide levels are abnormally elevated in age-dependent pathologies such as cardiovascular diseases, obesity and Alzheimer’s disease. Nevertheless, the potential impact of age on plasma ceramide levels has not yet been systematically examined. In the present study, we quantified a focused panel of plasma ceramides and dihydroceramides in a cohort of 164 subjects (84 women) 19 to 80 years of age. After adjusting for potential confounders, multivariable linear regression analysis revealed a positive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 59 publications
2
34
0
5
Order By: Relevance
“…The observed association between female gender and severe coronary artery stenosis was possibly resulted from estradiol-induced unbalance of ceramides. A recent study [31] using multivariable linear regression analysis revealed that Cer (d18:1/24:0) and Cer (d18:1/24:1) were increased over age in women. In women of all ages, but not in men, plasma Cer (d18:1/24:1) was negatively correlated with plasma estradiol.…”
Section: Discussionmentioning
confidence: 98%
“…The observed association between female gender and severe coronary artery stenosis was possibly resulted from estradiol-induced unbalance of ceramides. A recent study [31] using multivariable linear regression analysis revealed that Cer (d18:1/24:0) and Cer (d18:1/24:1) were increased over age in women. In women of all ages, but not in men, plasma Cer (d18:1/24:1) was negatively correlated with plasma estradiol.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro experiments further suggested that ceramide induced vasoconstriction by iPLA2, cyclooxygenase-1 and thromboxane synthase [50]. In addition, one clinical study found a significant correlation between plasma ceramide (Cer d18:1/16:0) and hypertension in postmenopausal women [48].…”
Section: Changes In Ceramide Metabolism In the Rat Aorta After Ovariementioning
confidence: 97%
“…The correlation between estrogen and ceramide has mainly been reported in breast cancer, serum, plasma and other tissues [46][47][48][49]. However, the effect of estrogen or ovariectomy on ceramide metabolism in vessels has never been reported.…”
Section: Changes In Ceramide Metabolism In the Rat Aorta After Ovariementioning
confidence: 99%
“…Ceramides constitute (on a weight basis) approximately 47% of the SC lipids [186]. Moisturizing treatment involves a four-step process: a) repairing the skin barrier, b) increasing water content, c) reducing TEWL and d) restoring the lipid barriers' ability to attract, hold and redistribute water.Interestingly, a statistically significant higher ceramide/cholesterol ratio was found for men than for women, as reported by Vozella et.al, 2019 [183]. Jensen et.al, 2005 reported reduced activities of ceramidegenerating epidermal acid sphingomyelinase (SMase) and ceramide synthase in the inner epidermis of aged skin, explaining its reduced capacity in barrier repair [182].…”
Section: G α-Lipoic Acidmentioning
confidence: 65%